The trespasses of property law. Issue 1 (10th July 2013) - Wall, Jesse
Abstract : The purpose of this article is to identify a limit to the appropriate application of property law to the use and storage of bodily material. I argue here that property law ought to be limited to protecting 'contingent rights' and that recent cases where property rights have been recognised in semen represent the application of property law beyond this limit. I also suggest how the law ought to develop in order to avoid the overextensive use of property law.